A Systematic Review of Laboratory Evidence for the Abuse Potential of Tramadol in Humans - Dunn, Kelly E.; Bergeria, Cecilia L.; Huhn, Andrew S.; Strain, Eric C. (Frontiers in Psychiatry, 2019)
Background: Tramadol is an opioid-analgesic that has shown epidemiological evidence of abuse. This review evaluates the evidence for tramadol abuse potential in humans. Methods: A systematic literature search for human abuse liability examinations of tramadol was conducted in September 2018 and yielded 13 total studies. Studies were all within-subject, double-blind, placebo-controlled human laboratory comparisons of tramadol to opioid comparators. Results are organized based upon the route of tramadol administration (oral, parenteral) and the participant population (persons with and without current opioid physical dependence). Outcomes were categorized into self-report ratings of positive and negative effects, observer-ratings of effects, time course of effects, likelihood tramadol was identified as an opioid, and tramadol self-administration. Results: Results indicated the relative abuse potential of tramadol was lower than the opioids to which it was compared. Tramadol produced highest positive effect ratings when administered orally to persons with no opioid physical dependence. Relative to other opioids, it produced substantial negative ratings, generally demonstrated a slower onset of effects, and was less likely to be identified by participants as an opioid, though it did produce a higher rate of self-administration relative to other opioids in the one study reporting that outcome. Results suggest that the abuse potential of tramadol is highest when it is administered orally to non-dependent individuals, and that it likely decreases as the dose increased and when it was administered parentally or to persons with opioid physical dependence. Conclusion: Taken together, individuals may be less likely than with other opioids to escalate tramadol doses, transition from oral to parenteral routes of administration, or continue using tramadol once opioid physical dependence develops. In that way, the human abuse potential of tramadol appears to be different from and lower than other opioid analgesic medications.